hi
Pote,
Part (a):
since the derivative is to be found in terms of 'x', and the integral given is in terms of the variable 't' with one of the ordinates as 'x', then it would appear intuitive to begin by integrating first, then differentiate the integral obtained:
Int[(4t^3 - 3t^2 + t -1)dt] from 'x' to '3' = [t^4 - t^3 + (1/2)t^2 - t] from 'x' to '3'
----->
Int = x^4 - x^3 + (1/2)x^2 - x - (3^4 - 3^3 + (1/2)3^2 -3)
the next step is to differentiate this integral with respect to 'x':
d(Int)/dx =
4x^3 - 3x^2 + x -1 ; note that
-(3^4 - 3^3 + (1/2)3^2 -3) of the integral is simply a constant.
Part (b):
same principle as that of
Part(a):
Int[(7 - 6t)^4 dt] from '2' to 'x' = [(-1/30)(7 - 6t)^5] from '2' to 'x'
----->
Int = (-1/30)(7 - 12)^5 + (1/30)(7 - 6x)^5
differentiate with respect to 'x':
d(Int)/dx =
-(7 - 6x)^4 ; note that
(-1/30)(7 - 12)^5 of the integral is simply a constant.
Part (c):
(i)
Differentiating V(x) to get V'(x):
V'(x) = d[(a-x)U(x)]/dx + d[Int[U(t)dt] from 'x' to '0']/dx
Now,
d[(a-x)U(x)]/dx can be found using the
product rule:
d[(a-x)U(x)]/dx =
(a-x).u(x) - U(x)
and,
d[Int[U(t)dt] from 'x' to '0']/dx can be found using the approach outlined in Parts (a) & (b):
let
W(t) be the
primitive of U(t) ;
ie. Int[U(t)dt] from 'x' to '0' = W(x) - W(0) ; but observe that
W(0) is a constant.
hence, d[Int[U(t)dt] from 'x' to '0']/dx = d(W(x) - W(0))/dx =
U(x)
Therefore: V'(x) = (a-x).u(x) - U(x) + U(x) =
(a-x).u(x)
(ii)
in
(i) you've shown that V'(x) = (a-x).u(x) ;
hence,
Int[V'(x) dx] from 'a' to '0' = Int[(a-x).u(x).dx] from 'a' to '0'
now, LHS = V(a) - V(0) ;
where V(x) = (a-x)U(x) + Int[U(t)dt] from 'x' to '0' =
(a-x)U(x) + W(x) - W(0)
ie. LHS = (a-a)U(a) + W(a) - W(0) - (a-0)U(0) - W(0) + W(0) =
W(a) - W(0) - a.U(0)
but since Int[U(x)dx] = W(x) ; then W(a) - W(0) = Int[U(x)dx] from 'a' to '0'
ie.
LHS = (Int[U(x)dx] from 'a' to '0') - a.U(0)
Therefore, substitute this expression for the LHS back:
(Int[U(x)dx] from 'a' to '0') - a.U(0) = Int[(a-x).u(x).dx] from 'a' to '0'
----->
Int[U(x)dx] from 'a' to '0' = a.U(0) + Int[(a-x).u(x).dx] from 'a' to '0'
as required.
hope that helps
[i hope you understand what i typed, some of the notation might be confusing for a while, so sorry about that.]
Edit:
FinalFantasy beat me to it as per usual, though i was typing out for all the parts of that question you posted, didn't realise you only needed help for
Part (c)...